2022
DOI: 10.9734/jeai/2022/v44i230799
|View full text |Cite
|
Sign up to set email alerts
|

Appraisal the Effect of NitrogenPhosphorus and Bio-fertilizers on Protein Contentin Seed of Garden Pea (Pisum sativum L.) cv. Arkel

Abstract: A field experiment was performed in the course of rabi  year 2017-18.to study the effect of nitrogen, phosphorus and biofertilizers on the protein content of seeds of garden peas (Pisum sativum L.) cv. Arkel. The experiment was set up in RBD, with 11 treatments in three replications comparing nitrogen and phosphorus levels, as well as bio-fertilizers, to the control.A significant increase in protein content from 15.60% to 22.06% when 20 kg per hectare N + 40 kgper hectare P + Rhizobium + PSB was applied (T5), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
1
0
0
Order By: Relevance
“…Similar findings were observed by [4] who observed that with the application of PSB there was greater root extension under higher availability of phosphorous and organic manure which might have helped in greater uptake of other nutrients especially micronutrients and secondary nutrients, enhanced photosynthesis, and increased number of pods per plant in pea. The results are in conformity with the findings of [11][12][13]19,28,29,35,[37][38][39] in pea.…”
Section: Yield Parameterssupporting
confidence: 92%
See 1 more Smart Citation
“…Similar findings were observed by [4] who observed that with the application of PSB there was greater root extension under higher availability of phosphorous and organic manure which might have helped in greater uptake of other nutrients especially micronutrients and secondary nutrients, enhanced photosynthesis, and increased number of pods per plant in pea. The results are in conformity with the findings of [11][12][13]19,28,29,35,[37][38][39] in pea.…”
Section: Yield Parameterssupporting
confidence: 92%
“…Enhanced pod length with the application of integrated nutrient management could be attributed to improved soil physical, chemical and biological properties and thus leading to higher availability of all plant nutrients which in turn results in higher yield contributing traits like pod length. Similar results were observed by [13,35,36] in pea, [22] in cowpea and [14] in french bean. The number of pods per plant is a prominent determination of yield in pea.…”
Section: Yield Parameterssupporting
confidence: 89%
“…The maximum available phosphorus of soil was recorded 38.70 and 36.28 kg ha -1 in treatment T 9 (NPK @ 100% + Biochar @ 100 %) and minimum available phosphorus of soil was recorded 21.45 and 19.34 kg ha -1 at 0-15 cm and 15-30 cm in treatment T 1 (NPK @ 0% + Biochar @ 0 %), respectively. Similar result has been recorded by [26,27,2].…”
Section: Available Nitrogen (Kg Ha -1 )supporting
confidence: 91%
“…23 and 190.55 kg ha -1 at 0-15 cm and 15-30 cm in treatment t 1 (npk @ 0% + biochar @ 0 %), respectively. Similar result has been recorded by [26,[27][28][29][30][31]2].…”
Section: Available Potassium (Kg Ha -1 )supporting
confidence: 88%
“…A positive effect of mineral fertilization on elements of pea yield structure (number of pods and seeds per plant) was also reported by Badr and Fayed [37]. In a study by Bunker et al [38], a combination of seed inoculation with Rhizobium and N 20 P 40 application increased the number of pods per plant and seeds in pods by 57.2% and 34.2%, respectively, compared to the control variant. Also, Khatana et al [39] found that the highest number of pods formed on black gram (Vigna munga L.) plants could be obtained with the combined application of NPK and seed inoculation with Rhizobium.…”
Section: Discussionsupporting
confidence: 61%